2013
DOI: 10.1007/s11999-012-2594-y
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative Cartilage Degeneration Predicts Outcome 12 Months After Hip Arthroscopy

Abstract: Background When considering arthroscopic surgery for

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
48
0
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(53 citation statements)
references
References 23 publications
4
48
0
1
Order By: Relevance
“…Our finding builds on those from systematic reviews14 37 38 and recent studies that report lower preoperative to postoperative improvements in those with severe chondropathy, compared to those with mild39 or no chondropathy 13 40. Since hip chondropathy at arthroscopy represents early-onset hip OA, it appears that those with more advanced chondropathy have progressed further along the disease continuum of hip OA.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Our finding builds on those from systematic reviews14 37 38 and recent studies that report lower preoperative to postoperative improvements in those with severe chondropathy, compared to those with mild39 or no chondropathy 13 40. Since hip chondropathy at arthroscopy represents early-onset hip OA, it appears that those with more advanced chondropathy have progressed further along the disease continuum of hip OA.…”
Section: Discussionsupporting
confidence: 75%
“…Our modest sample size is a limitation, and these findings need to be replicated in larger studies. Since the Outerbridge grading scale of cartilage defects was not originally reported for cartilage defects in the acetabulum,13 47 future studies could consider using grading systems established specifically for acetabular defects seen at hip arthroscopy 48. We did not perform additional subgroup analysis on each of the groups to determine the effect of types of surgical intervention, type of FAI or other coexisting pathology on outcomes, due to the sample size of this study 49.…”
Section: Discussionmentioning
confidence: 99%
“…During recent years we have seen an increase in the number of hip arthroscopies mainly due to a better understanding of femoro acetabular impingement (FAI) [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
“…Box 1 highlights some of the key articles that have influenced the evolution of hip arthroscopy.
Key articles on hip arthroscopyIn 1987, Glick et al 2 described hip arthroscopy by the lateral approach.Thomas Byrd3 published a series using supine positioning for hip arthroscopy.McCarthy and Busconi88 found that hip arthroscopy resulted in statistically significant improvement for patients with a hip click/mechanical acetabular symptoms and loose bodies.Clarke et al 75 demonstrated that hip arthroscopy was a relatively safe procedure with minimal complications.Byrd and Jones89 performed a prospective analysis of hip arthroscopy to treat a variety of disorders demonstrating reasonable success at 10 years follow-up.Ganz et al 33 identified femoroacetabular impingement as a cause for osteoarthritis of the hip.Phillipon et al 28 demonstrated that arthroscopically repaired labral tissue was capable of healing in an ovine model.Telleria et al 90 described the normal anatomic location of the hip capsular ligaments and their relationship to the routine anatomic portals used during hip arthroscopy.Telleria et al 78 determined that the risk of sciatic nerve injury was more related to the amount of traction than the duration.Egerton et al 91 found that the presence of cartilage degeneration was correlated with poorer outcomes following hip arthroscopy.Kemp et al 92 performed a systematic review demonstrating inferior results of hip arthroscopy in patients with osteoarthritis.
…”
Section: Introductionmentioning
confidence: 99%
“…Egerton et al 91 found that the presence of cartilage degeneration was correlated with poorer outcomes following hip arthroscopy.…”
Section: Introductionmentioning
confidence: 99%